2015
DOI: 10.1021/acs.jpca.5b05564
|View full text |Cite
|
Sign up to set email alerts
|

Bond Energies and Thermochemical Properties of Ring-Opened Diradicals and Carbenes of exo-Tricyclo[5.2.1.02,6]decane

Abstract: Exo-tricyclo[5.2.1.0(2,6)]decane (TCD) or exo-tetrahydrodicyclopentadiene is an interesting strained ring compound and the single-component high-energy density hydrocarbon fuel known as JP-10. Important initial reactions of TCD at high temperatures could cleave a strained carbon-carbon (C-C) bond in the ring system creating diradicals also constrained by the remaining ring system. This study determines the thermochemical properties of these diradicals (TCD-H2 mJ-nJ where m and n correspond to the cleaved carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…It can be explained by the molecular structure that the greater the number of rings in the compound structures, the greater the repulsion between the atoms and the ring tension; meanwhile, they will be more unstable and more prone to cracking under high-temperature conditions. Another reasonable explanation has been reported from some studies that the C–C bond dissociation energy of JP-10 (322.17–418.4 kJ/mol) is higher than that of THTCPD (17.42–200.53 kJ/mol), which further confirms our results. In addition, the initial conversion of the JP-10/THTCPD mixtures were almost the same, because of it being the only reaction of THTCPD self-dissociation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It can be explained by the molecular structure that the greater the number of rings in the compound structures, the greater the repulsion between the atoms and the ring tension; meanwhile, they will be more unstable and more prone to cracking under high-temperature conditions. Another reasonable explanation has been reported from some studies that the C–C bond dissociation energy of JP-10 (322.17–418.4 kJ/mol) is higher than that of THTCPD (17.42–200.53 kJ/mol), which further confirms our results. In addition, the initial conversion of the JP-10/THTCPD mixtures were almost the same, because of it being the only reaction of THTCPD self-dissociation.…”
Section: Resultssupporting
confidence: 93%
“…There is no significant difference in the decomposition rate of JP-10/THTCPD and that of THTCPD at the initial decomposition stage (before 600 °C), because the only reaction is THTCPD self-dissociation. At the initial stage of the binary fuel pyrolysis, THTCPD is first cracked through the breaking of the C−C bond, because the C−C bond dissociation energy of JP-10 (322.17−418.4 kJ/mol) 44 is higher than that of THTCPD (17.42−200.53 kJ/mol). 24 However, as the reaction continues, the free radicals generated by THTCPD are more likely to react with JP-10 via H-abstraction reaction, because of the high molar ratio of JP-10 (59.77% in 50% JP-10/50% THTCPD) in the binary fuels, which can significantly promote the JP-10 pyrolysis.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…The single-component hydrocarbon fuel Jet Propellant-10 (JP-10) is used in detonation engines, missiles, and supersonic combustion ramjets, where a fuel is required to have high thermal stability, high-energy density, and low freezing point. Because of its broad applications, the principal constituent of JP-10, tricyclo­[5.2.1.0 , ]­decane ( exo -tetrahydrodicyclopentadiene; exo -TCD; C 10 H 16 ; Figure ), has attracted significant attention of researchers, and numerous experimental, theoretical, and modeling studies of its pyrolysis and combustion have been reported in the literature. A detailed overview on the JP-10 studies was provided in our recent publication, and here we only briefly reiterate its key points.…”
Section: Introductionmentioning
confidence: 99%
“…Ritter and Bozzelli developed THERM (THermo Estimation for Radicals and Molecules) based on Benson’s GA method, which can be used as illustrated in Figure . Bozzelli and co-workers have also studied the thermochemistry of different classes of species including sulfurated, nitridated, fluorinated, oxygenated, and saturated hydrocarbons, Table . Enthalpies of formation, entropies, and heat capacities have been compiled for certain classes of species using density functional theory (DFT) and composite compound methods, from which bond dissociation energies (BDEs) of similar type of bonds and GAVs were systematically reported and compared.…”
Section: Introductionmentioning
confidence: 99%